Gambaran Tingkat Kontrol Asma Pasien Asma di Puskesmas 23 Ilir Palembang - Utama, Yofa Anggriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the effect of slow deep breathing therapy on the level of asthma control at Puskesmas 23 Ilir Palembang. The research method used was a quasi experiment, with a one group pre-test - post-test design on a sample of 30 respondents. The results of this study found that there was an effect on the level of asthma control before and after slow deep breathing therapy at Puskesmas 23 Ilir Palembang.